SISTEM PENJADWALAN KULIAH DENGAN MENGGUNAKAN ALGORITMA GENETIKA - Simamora, Purwanto; ., Tulus; Batubara, Fakhruddin R. (JURNAL PENELITIAN SAINTIKA, 2013)
Course scheduling is process of placing courses into available time-and classroom slots. As number of course activities and requirement needed increase, the solution to scheduling problem become more complicated. In order to get a good course scheduling, there are some important components such as lecturer, subject, student, curriculum, classroom and time. The limitation of rooms and time is often become a problem in making the course scheduling. The addition number of the students and the subjects due to the application of the new curriculum, and the other activity in university give the effects the using of times and rooms. Course scheduling systems which is adaptable in every changing that happened. The course scheduling must be able to overcome the limitation of each component such as the number of the lecturer, times and rooms. This research uses two methods in making the course scheduling which are by using the scheduling algorithm and without using the scheduling algorithm. These two methods will be combined into the genetic algorithm in order to get a course scheduling which can reduce the problem in the availability of rooms and times.             The research result shows without using the schedule algorithm these are 2 faults appear in the time schedule and the minimum number of room which used is 9 rooms and converged in the 127th generation. But, by using the schedule algorithm the number of the fault is no longer appear, the using of the room becomes 8 rooms and converget in the 85th generation. It is concluded that making the course scheduling by combining the schedule algorithm and genetic algorithm is a right method in reducing the time fault and minimizing the using of the room.